The Role of Administrative Governance Principles in Achieving Institutional Excellence: An Applied Study on the Saudi Telecom Company in Jeddah. - Yagob Yussef, Asseri Maree (IJRDO - Journal of Social Science and Humanities Research, 2024)
The study aimed to identify the role of administrative governance principles with their dimensions (transparency, accountability, integrity, participation) in achieving institutional excellence from the point of view of employees of the Saudi Telecom Company in Jeddah Governorate. The study relied on the descriptive analytical approach, and used the questionnaire as the main tool for collecting data from a random sample. There were (164) employees of the administrative departments at the Saudi Telecom Company in Jeddah. The data was analyzed using the SPSS program, and the results of the study concluded that the role of the principle of transparency in achieving institutional excellence in the company was at a very high level, with an approval rate of (87%), and that the principle of accountability was at a high level. High and approval rate (83.2%), the principle of integrity came at a high level and approval rate (80%), and the principle of participation came at a high level and approval rate (78.2%). The results also showed that the level of institutional excellence at the Saudi Telecom Company in Jeddah Governorate was at a high level with an approval rate of (81.4%). The results also reached acceptance of the main hypothesis, that is, there is a statistically significant relationship at the 0.05 significance level between the principles of administrative governance in its four dimensions and achieving excellence. Corporate Institution of Saudi Telecom Company in Jeddah Governorate. The study recommended the necessity of conducting a study similar to the current study as an applied study on all other organizations and telecommunications companies, while conducting more future studies on the obstacles that prevent telecommunications companies from adhering to the principles of governance.